ANALYSIS COMPETENCE OF VILLAGE OFFICIALS ON THE PERFORMANCE OF VILLAGE FUND MANAGEMENT IN BANYUMAS REGENCY - Kartika Dwi Chandra Sari; Alan Bayu Aji (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Village government has clear objectives and achievements in government administration. Organizational effectiveness is important in the realization of the goals and achievements of the village government. From the perspective of human resources, the effectiveness of an organization can be seen from the competencies possessed by village officials. The purpose of this study was to determine the effectiveness of the use of Village Funds by looking at the average competency and performance of village fund management in the village apparatus of the Banyumas Regency. In this study, the questionnaire has gone through the stages of validity and reliability testing, classical assumption test and multiple regression test. The conclusion is that knowledge and skills do not have a significant effect on village management performance. while the attitude variable has a significant effect on the performance of village management. Suggestions for the village government, in improving the competence of village officials in the Banyumas region in work, it is necessary to have training in accordance with the needs of the Village Apparatus, so that knowledge, insight and skills increase. This is to increase the average number of job analysis skills.